Effect of moderate electric field on glucoamylase-catalyzed hydrolysis of corn starch: Roles of electrophoretic and polarization effects. (January 2022) - Li, Dandan; Wu, Zhengzong; Wang, Pei; Xu, Enbo; Cui, Bo; Han, Yongbin; Tao, Yang
Abstract: This study aimed to investigate the effect of moderate electric field (MEF, 0–10 V/cm, 50 Hz) on the glucoamylase-catalyzed hydrolysis of corn starch. The underlying mechanism was explored by monitoring changes in the hydrolysis rate, glucoamylase activity, substrate structure, temperature profiles, and hydrolysate properties. The results suggested that the hydrolysis rate highly depended on the MEF intensity. Low-intensity MEF (0–5 V/cm) increased glucoamylase activity by 7.1–22.4% by inducing mild electrophoretic and polarization effects, which resulted in the formation of porous starch. Although high-intensity MEF accelerated the thermal inactivation of glucoamylase, it completely destroyed starch granules due to the extensive ohmic heating; hence, a significant improvement in the hydrolysis efficiency and dramatic decreases in the pasting viscosity, gelatinization enthalpy, and thermo-stability were observed. Overall, this study clarified the mechanism of MEF-assisted enzymatic hydrolysis, which might contribute to expanding the applications of electric field-based techniques in starch modification. Graphical abstract: Image 1 Highlights: Moderate electric field (MEF) enhanced glucoamylase-catalyzed hydrolysis of corn starch. Low-intensity MEF slightly increased the hydrolysis mainly by activating glucoamylase. High-intensity MEF largely improved the hydrolysis mainly by destroying starch structure. Mild electrophoretic and polarization effects activated glucoamylase. Extensive electrophoretic motion and polarization intensified enzyme deactivation.